Common random fixed points of compatible random operators - Ismat Beg; Mujahid Abbas (International Journal of Mathematics and Mathematical Sciences)
We construct a random iteration scheme and study necessary conditions for its convergence to a common random fixed point of two pairs of compatible random operators satisfying Meir-Keeler type conditions in Polish spaces. Some random fixed point theorems for weakly compatible random operators under generalized contractive conditions in the framework of symmetric spaces are also proved.